2016
DOI: 10.1248/bpb.b15-00882
|View full text |Cite
|
Sign up to set email alerts
|

The Bisphosphonates Clodronate and Etidronate Exert Analgesic Effects by Acting on Glutamate- and/or ATP-Related Pain Transmission Pathways

Abstract: Key words analgesic effect; clodronate; etidronate; phosphate transporter; ATP; glutamate Bisphosphonates (BPs) are used against various boneresorptive diseases, and the nitrogen-containing BPs (N-BPs) have much more powerful anti-bone-resorptive effects than the non-nitrogen-containing BPs (non-N-BPs) 1) (Fig. 1). However, N-BPs have inflammatory and/or necrotic effects, including fever, musculoskeletal pain, direct injuries to esophageal and gastric tissues, and osteonecrosis of the jaw.2) N-BPs, having ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Clo and Eti exert analgesic effects via inhibition of phosphate transporters of the SLC17 family. 37) Those findings, together with the ones made in the present study, may suggest that Eti and Clo should be reappraised as safe and useful drugs for osteoporosis.…”
Section: )supporting
confidence: 75%
“…Clo and Eti exert analgesic effects via inhibition of phosphate transporters of the SLC17 family. 37) Those findings, together with the ones made in the present study, may suggest that Eti and Clo should be reappraised as safe and useful drugs for osteoporosis.…”
Section: )supporting
confidence: 75%
“…86) Thus, it is likely that Eti and Clo exhibit their analgesic effects by inhibiting these transporters. Indeed, our recent study supports this idea 17) (Fig. 6).…”
Section: Analgesic Effects Of Eti and Closupporting
confidence: 67%
“…injected N-BPs tested (4 mM) are reduced by co-injection with clodronate (1-16 mM), 20) and that the inflammatory and/or necrotic effects of locally injected N-BPs, including zoledronate, are likewise reduced by co-injection with clodronate. 18,19,21,22) So, we compared the effects of clodronate on the augmented production of IL-1α and IL-1β seen in mice given i.v. zoledronate and then (3 d later) i.v.…”
Section: Effects Of IV Lps On Il-1α and Il-1β Productions In Mice Pmentioning
confidence: 99%
“…Effect of Clodronate on the Increased IL-1α and IL-1β Production Induced by Zoledronate Plus LPS Our pharmacological results suggest that N-BPs may enter soft-tissue cells via the phosphate transporter families SLC20 and/or SLC34, and that clodronate inhibits this entry and thereby reduces or prevents the inflammatory and/or necrotic effects of N-BPs. 21,22) SLC20 transporters are known to be present ubiquitously throughout the body. 32,33) In the present study, we found that 20 mM clodronate, when co-injected with 4 mM zoledronate, can reduce the augmented production of IL-1α and IL-1β in bone and spleen induced when i.v.…”
Section: Effects Of Lps On the Production Of Il-1α And Il-1β In Mice mentioning
confidence: 99%
See 1 more Smart Citation